Strategi Pencegahan dan Pemberantasan Korupsi di Pemerintah Kota Kupang, Provinsi Nusa Tenggara Timur, Indonesia - Habaora, Fellyanus; Riwukore, Jefirstson Richset; Manafe, Hilda; Susanto, Yohanes; Yustini, Tien (Jurnal Aspirasi, 2020)
Kupang is the most corrupt city based on a survey by Transparency International Indonesia. The problem is what are the causes of corruption in Kupang City? and what are the strategies the Kupang City Government could adopt to prevent and eradicate corruption in its regions? This research identifies corruption behavior based on terminology, behavioral factors, a mode that is often used to commit corruption, and what must be done to overcome it The method used in this research was an explanatory method using secondary data. Qualitative analysis was then conducted using SWOT analysis. Results showed that corruption is an action to enrich themselves, their families, groups, and corporations by violating rules, norms, and human rights through the exploitation of economic, political, socio-cultural, and environmental resources by maximizing the potential of their resources (position, network, and power). Factors that cause corruption are individual motivations and poor government organization systems and will increase the influence of corruption if it is supported by an environment in which individuals and poor systems are located. Based on this, the strategies that can be carried out by Kota Kupang Government are to immediately carry out an MoU with law enforcement institutions; to use electronic or online systems for all financial transactions within the government; to form a task force against extortion in the government; to enforce financial reporting for all officials within the government; to have a more efficient government budget for a dual and unnecessary function to open access for public monitoring through electronic database, and to have an integrity pact-based performance measurement. AbstrakPenelitian ini mengidentifikasi perilaku korupsi berdasarkan terminologi, faktor penyebab perilaku, modus yang sering dilakukan untuk melakukan korupsi, dan apa yang harus dilakukan untuk mengatasinya. Metode yang digunakan untuk melakukan penelitian ini adalah penelitian eksplanatif menggunakan data sekunder. Kemudian dianalisis secara kualitatif berdasarkan hasil analisis SWOT. Hasil penelitian menunjukan bahwa korupsi adalah tindakan untuk memperkaya diri, keluarga, kelompok, dan korporasinya dengan cara melanggar aturan, melanggar norma, melanggar hak asasi manusia melalui eksploitasi sumberdaya ekonomi, politik, sosial budaya, dan lingkungan hidup dengan memaksimalkan potensi sumberdaya yang dimiliki (jabatan, jaringan, dan kekuasaan). Faktor penyebab korupsi adalah motivasi individu dan sistem organisasi pemerintah yang buruk, dan akan semakin meningkat pengaruh korupsi jika didukung oleh lingkungan dimana individu dan sistem yang buruk berada. Berdasarkan hal tersebut maka strategi yang dapat dilakukan oleh Pemerintah Kota Kupang adalah segera melakukan Memorandum of Understanding dengan lembaga penegakan hukum, segala transaksi keuangan di pemerintahan menggunakan transaksi elektronik atau online, pemerintah membentuk gugus tugas pemberantasan pungli di pemerintahan, memberlakukan pelaporan keuangan pada pejabat di lingkup pemerintahan, efisiensi anggaran pemerintahan yang ganda fungsi dan tidak bermanfaat, membuka akses pemantauan publik melalui base data elektronik, dan pengukuran kinerja berbasis pakta integritas.